العمارة المتنقلة رؤيا جديدة لعمارة مستدامة - أحمد عامر جبري (Tishreen University, 2019)
مع ظهور مفاهيم العمارة المستدامة وتطور أساليب الحياة والتقنيات الحديثة, أعيدت إلى الأذهان أساليب من العمارة لم يكن من المتوقع أن تحظى بالاهتمام المتزايد للباحثين عن تطوير مفاهيم جديدة وأساليب تتوافق مع الحياة المستقبلية, وبسبب المعطيات الجديدة ظهر مفهوم العمارة المنقولة أو المحمولة, التي تسمح بإقامة منشأة أو تنظيم موقع ما بطريقة مؤقتة, وهي قابلة للاستخدام في بيئة يصنعها الإنسان, وتأثيرها قابل للاستمرار مدة طويلة , وكان لا بد من أن نتوقف عند هذه الظاهرة لدراسة جوانبها الإيجابية كما السلبية, لتحديد إمكانيتها لتلبية ما تصبو إليه هذه العمارة. يستعرض البحث تطور هذه العمارة ومفاهيمها واتجاهاتها، وأمثلة على تطبيقاتها وتأثير التقنيات والمواد الحديثة, في تصميماتها، وصولاً إلى الحيز المكاني الجديد لهذه العمارة. ويخلص البحث إلى أن الحراك الاجتماعي و الثقافي كانا المحور الديناميكي لتطور العمارة المنقولة أو المحمولة, فهي توجه الدعوة إلى العالم لإلغاء الحدود والتمتع بحياة أكثر إنسانية, و قدمت العلوم والتقنيات الإمكانيات التنفيذية لهذه العمارة , كما أن مقياس نجاح هذه العمارة, يكمن في أنها كانت إنسانية، وحققت الهدف الجوهري لها, حين قدمت الحل لمن حلت بهم الكوارث الطبيعية أو رحلتهم الحروب عن مدنهم وبلادهم.       With the emergence of concepts of sustainable architecture and the evolution of life styles and modern techniques returned to mind the styles of architecture which were not expected to receive the growing interest of researchers for the development of new concepts and methods compatible with the future life. Because of new data the concept of architecture mobile or portable emerged, which allows erecting a building or organizing a site temporarily, which is usable in a man-made environment, and its effectuation is long-term viable, and it was necessary to stop at this phenomenon to study its positive and negative aspects, to determine its possibility to meet the aspiration of this architecture. This research reviews the evolution of this architecture, its concepts and trends, examples of its applications, the effectuation of technology and modern materials on its designs, and the new locative space for this architecture. The study concludes that social and cultural mobility are the dynamic axis for the evolution of the architecture mobile or portable. It is an invitation to the world to abolish the limits and enjoy a life that is more humane, and science and technology provide the Executive capabilities to this architecture. The measure of the success of this architecture lies in the fact that it was humane and made its ultimate target when it provided the solution for those who got natural disasters or  were forced to leave their towns and countries because of wars.